CORRELATION BETWEEN THE KNOWLEDGE LEVEL OF ADOLESCENT WOMEN ABOUT REPRODUCTIVE HEALTH TOWARDS ATTITUDE IN EARLY MARRIAGE - Itdinah Rara Karima; Atika Atika; Rize Budi Amalia (UNIVERSITAS AIRLANGGA, 2022)
Abstract Adolescent reproductive health is a state of the system, function, and process of adolescent reproduction. Attitudes in early marriage can affect readiness for marriage. The purpose of this study was to analyze the correlation between the level of knowledge of adolescents about reproductive health on attitudes in early marriage. The design of this study was a cross-sectional observational analytic. The population in this study were teenage girls in class X and XI SMA GIKI 2 Surabaya. The sample is 96 people with a simple random sampling technique. The analytical data used are chi-square and contingency coefficients. The results showed that 50 (52.1%) and 85 (88.5%) had positive attitudes, and there was a correlation between the attitude level in early marriage (0.030<0.05) and the contingency coefficient = 0.271 that there was a relationship between the level of knowledge about reproductive health on attitudes in early marriage at SMA GIKI 2 Surabaya. Suggestions for schools to improve educational programs on reproductive health. Keywords: Adolescent, Attitude, Knowledge Level